Community participation in primary health care projects of the Muldersdrift Health and Development Programme - M. Barker; H. Klopper (AOSIS, 2007)
After numerous teething problems (1974-1994), the Department of Nursing Education of WITS University took responsibility for the Muldersdrift Health and Development Programme (MHDP). The nursing science students explored and implemented an empowerment approach to community participation. The students worked with MHDP health workers to improve health through community participation, in combination with primary health care (PHC) activities and the involvement of a variety of community groups. As the PHC projects evolved overtime, the need arose to evaluate the level of community participation and how much community ownership was present over decision-making and resources. This led to the question "What was the level of community participation in PHC projects of the MHDP?" Based on the question the following objectives were set, i.e. i) to evaluate the community participation in PHC initiatives; ii) to provide the project partners with motivational affirmation on the level of community participation criteria thus far achieved; iii) to indicate to participants the mechanisms that should still be implemented if they wanted to advance to higher levels of community participation; iv) to evaluate the MHDP's implementation of a people-centred approach to community participation in PHC; and v) the evaluation of the level of community participation in PHC projects in the MHDP. An evaluative, descriptive, contextual and quantitative research design was used. Ethical standards were adhered to throughout the study. The MHDP had a study population of twentythree (N=23) PHC projects. A purposive sample of seven PHC initiatives was chosen according to specific selection criteria and evaluated according to the "Criteria to evaluate community participation in PHC projects" instrument (a quantitative tool). Structured group interviews were done with PHC projects' executive committee members. The Joint Management Committee's data was collected through mailed self-administered questionnaires. Validity and reliability were ensured according to strict criteria. Thereafter results were analysed and plotted on a radiating arm continuum. The following factors had component scores: organization, leadership, resources, management; needs and skills. A spider graph was produced after each factor's continuum was connected in a spoke figuration that brought them together at the base where participation was at its most narrow. The results are presented and a graph and discussion is provided on each of the PHC projects.